Association of Influenza Vaccination on Decreased Stillbirth Rate - Wortman, Alison C.; Casey, Brian M.; McIntire, Donald D.; Sheffield, Jeanne S. (American Journal of Perinatology, 2015)
Objective We have previously shown a decrease in the overall stillbirth rate at our institution in women receiving the seasonal influenza vaccine during pregnancy. The goal of this study was to ascertain factors associated with this decrease.Study Design This was a retrospective cohort study examining the stillbirth rate, etiology, autopsy findings, and placental pathology in pregnant women receiving the seasonal trivalent inactive influenza vaccine during five influenza seasons between 2003 and 2008. All stillbirths at our institution are investigated by a committee and an etiology is assigned. Autopsy is offered to all patients and placental evaluation is performed routinely.Results During the study period, 8,690 pregnant women received the seasonal influenza vaccine antepartum and delivered at our institution. Thirty of these births were complicated by stillbirth as compared with 436 stillbirths in the 76,153 women not vaccinated (0.35 vs. 0.57%, p = 0.006). No association was identified between assigned causes of stillbirth when comparing vaccinated and nonvaccinated women.Conclusion No specific etiology commonly associated with stillbirth was identified to have been affected by maternal antepartum influenza vaccination.
Keywords: pregnancy; influenza vaccine; stillbirth; benefit